2021
DOI: 10.1109/toh.2021.3077619
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Pseudo-Haptics: Haptic Feedback Design and Application Proposals

Abstract: In the last two decades, the design of pseudo-haptics as a haptic presentation method that does not require a mechanical feedback device has been proposed in various research papers. Moreover, applications using pseudo-haptics have been proposed and evaluated in various contexts. However, the findings from these studies have not yet been comprehensively organized in a survey paper in the recent times. In this article, findings from a series of individual prior studies were summarized from the design through to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 91 publications
(121 reference statements)
1
13
0
Order By: Relevance
“…Since VE and haptics are complementary to each other in many applications, it is necessary to conduct investigations on the relationship of these two technologies. More research should be undertaken to understand when the desired effect can be obtained by pseudo-haptics (i.e., "illusional haptic perceptions evoked by human vision" [167]) and when an actual haptic feedback is required for better realism. In addition, researchers should find ways for better synchronization of haptic and audio/video effects.…”
Section: ) Filling the Research Gapmentioning
confidence: 99%
“…Since VE and haptics are complementary to each other in many applications, it is necessary to conduct investigations on the relationship of these two technologies. More research should be undertaken to understand when the desired effect can be obtained by pseudo-haptics (i.e., "illusional haptic perceptions evoked by human vision" [167]) and when an actual haptic feedback is required for better realism. In addition, researchers should find ways for better synchronization of haptic and audio/video effects.…”
Section: ) Filling the Research Gapmentioning
confidence: 99%
“…More recently, Li et al [ 8 ] developed a surgical training system that employed pseudo-haptics to identify tumors upon palpation, in which the firmness of the tumor was presented using pseudo-haptics. Although a complete review of pseudo-haptics is beyond the scope of this article, Ujitoko and Ban [ 9 ] provide a recent and thorough review of the design and application of pseudo-haptics, focusing on three categories of use (training, assistance, and entertainment). They observed that the number of pseudo-haptics applications for training are far less than those applied to entertainment and assistance (e.g., navigation on touch-screen interfaces, and its use to influence the memorization of important knowledge), or entertainment [ 9 ].…”
Section: Editorialmentioning
confidence: 99%
“…Although a complete review of pseudo-haptics is beyond the scope of this article, Ujitoko and Ban [ 9 ] provide a recent and thorough review of the design and application of pseudo-haptics, focusing on three categories of use (training, assistance, and entertainment). They observed that the number of pseudo-haptics applications for training are far less than those applied to entertainment and assistance (e.g., navigation on touch-screen interfaces, and its use to influence the memorization of important knowledge), or entertainment [ 9 ]. This begs the question, can pseudo-haptics provide a viable alternative to complex expensive haptic devices required to facilitate psychomotor skill development in the virtual domain?…”
Section: Editorialmentioning
confidence: 99%
“…In this paper, inspired by 2D slider interaction, we propose the Rubber Slider metaphor, a novel, enhanced, pseudo-haptic control interface. The Rubber Slider metaphor gives better control to users over the displayed time range thanks to the additional degree of freedom and the pseudo-haptic feedback [4].…”
Section: Introductionmentioning
confidence: 99%